A representação da informação por meio da descrição arquivística: um estudo nos arquivos permanentes públicos de João Pessoa - Silva, Katiane Vieira da (2019)
Information is the object of reflection, research and investigation in different areas of knowledge, including Information Science and Archivology. The history of archives and their evolution are directly linked to progress and economic and social growth, being a differential that provides access to citizens' rights, accounting for the custody of individual and collective information, recognized as custodians of memory. Given this reality, this research is motivated by the perception of the importance of representation, archival description and the elaboration of research instruments, because through them users will have access to document content and information retrieval more efficiently and effectively. This research aims to analyze the use and applicability of archival description norms in permanent archives in the city of João Pessoa. Methodologically, this study has a qualitative approach, descriptive and in terms of sources, is classified as documentary and field research, making use of nonparticipant observation as a technique for data collection. The studied universe consisted of six permanent archives, registered in the National Register of Archival Custodians of the National Archives Council (CONARQ), located in the city of João Pessoa, state of Paraíba. They are: Archive of Governors José Casa Americo Foundation; Ecclesiastical Archive of Paraíba; Paraíba File and Documentation Operational Management; Citizenship and Human Rights Center; Regional Superintendence of Labor and Employment in Paraíba; and Federal University of Paraíba - Central Archive. From the investigation we could identify that only two archives use the Archival Description Standards and two other archives have Research Instruments. Although part of the archives analyzed have their peculiarities and difficulties regarding the representation of their collections, they remain open and fulfill their social role, preserving the political, social, historical and cultural memory of Paraíba.